Lycopene activates antioxidant enzymes and nuclear transcription factor systems in heat-stressed broilers - Şahin, Kazım; Orhan, C.; Tuzcu, M.; Şahin, Nurhan.; Hayirli, A.; Bilgili, S.; Küçük, Ömer (Elsevier, 2016)
This study was conducted to evaluate the effects of dietary lycopene supplementation on growth performance, antioxidant status, and muscle nuclear transcription factor [Kelch like-ECH-associated protein 1 (Keap1) and (erythroid-derived 2)-like 2 (Nrf2)] expressions in broiler chickens exposed to heat stress (HS). A total of 180 one-day-old male broiler chicks (Ross 308) were assigned randomly to one of 2 x 3 factorially arranged treatments: two housing temperatures (22 degrees C for 24 h/d; thermoneutral, TN or 34 degrees C for 8 h/d HS) and three dietary lycopene levels (0, 200, or 400 mg/kg). Each treatment consisted of three replicates of 10 birds. Birds were reared to 42 d of age. Heat stress caused reductions in feed intake and weight gain by 12.2 and 20.7% and increased feed efficiency by 10.8% (P < 0.0001 for all). Increasing dietary lycopene level improved performance in both environments. Birds reared under the HS environment had lower serum and muscle lycopene concentration (0.34 vs. 0.50 mu g/mL and 2.80 vs. 2.13 mu g/g), activities of superoxide dismutase (151 vs. 126 U/mL and 131 vs. 155 U/mg protein), glutathione peroxidase (184 vs. 154 U/mL and 1.39 vs. 1.74 U/mg protein), and higher malondialdehyde (MDA) concentration (0.53 vs. 0.83 mu g/mL and 0.78 vs. 0.45 mu g/mg protein) than birds reared under the TN environment. Changes in levels of lycopene and MDA and activities of enzymes in serum and muscle varied by the environmental temperature as dietary lycopene level increased. Moreover, increasing dietary lycopene level suppressed muscle Keap1 expression and enhanced muscle Nrf2 expression, which had increased by 150% and decreased by 40%, respectively in response to HS. In conclusion, lycopene supplementation alleviates adverse effects of HS on performance through modulating expressions of stress-related nuclear transcription factors.
Keywords: lycopene; heat stress; anti-oxidant status; broiler